Analysis of the Physical, Chemical and Microbiological parameter of Peat Water Processed by the Single Flow Ultrafiltration - Wianto, Totok; Nugrahadi, Dodon Turianto; Wahyono, Sri Cahyo; Gunawan, Gunawan; Azwari, Ayu Riana Sari; Arrahimi, Ahmad Rusadi; Apriana, Susi (Lambung Mangkurat University Press, 2024)
Peatlands have a crucial role in the global regulation of climate, the sequestration of carbon, and the conservation of biodiversity. Daily human activities and climate change have caused various environmental changes and ecological relationships for peatlands. An important thing to worry about is the decline in water quality, which harms the health and welfare of local communities that depend on clean water sources and drinking water from natural water. Additionally, the escalating demand for clean water necessitates substantial efforts in processing peatland water resources. The degradation in water quality harms the ecology and health of humans who use it for daily needs. Single Flow Ultrafiltration technology has emerged as a promising water treatment method, showing great potential in treating peat water while maintaining the ecological balance of peatlands. This research aims to evaluate the effectiveness of a combined treatment process consisting of filtration, absorption, microfiltration, and single-flow ultrafiltration. The application of this technology is carried out in the South Kalimantan region, with water processing stages, namely raw water filtration, semi-finished raw water filtration, ultrafiltration, and an ultraviolet irradiation process at the final stage so that the water is ready for consumption. Using both techniques, empirical methodologies were utilized to analyze the results of water quality and production capacity. This study proposes single-flow ultrafiltration to treat peat water for daily use. This research shows that the single-stream ultrafiltration treatment method for peat water gives a better water quality result than ordinary ultrafiltration treatment. This is indicated by the percentage difference in decreasing TDS values by 149%, turbidity by 200%, and color by 500%, increasing pH by 14.9%, decreasing nitrite by 135%